High Spectral Resolution Spectroscopy of Sprites: A Natural Probe of the Mesosphere. Issue 4 (23rd February 2018) - Gordillo‐Vázquez, F. J.; Passas, M.; Luque, A.; Sánchez, J.; van der Velde, O. A.; Montanyá, J.
Abstract: We present the first high spectral resolution (0.24 nm) spectra of sprites. These spectra were recorded in Europe in the summers and falls of 2015 and 2016 and during January 2017. The use of high spectral resolution has allowed us to resolve for the first time the internal (vibrorotational) structure of the sprite molecular N2 first positive system and to quantify the local gas (rotational) temperature of the mesosphere under the influence of sprites revealing that there is no measurable heating of the atmosphere associated to sprites at the altitudes explored. The temperatures of the explored region of the mesosphere range between 149 K ± 10 K and 226 K ± 20 K. The recorded spectroscopic data also provide valuable quantitative information on the concentrations of some of the vibrational levels of molecular nitrogen involved in transient red‐near‐infrared optical emissions from sprites. The regions of the transient luminous events recorded with our spectrograph (equipped with a horizontally oriented slit) correspond to altitudes in the 66 km to 74 km ± 5 km range. Key Points: High spectral resolution (0.24 nm) spectra of sprites are presented High‐resolution spectroscopy has allowed us to resolve for the first time the internal (vibrorotational) structure of sprite FPS N2 emissions The temperatures of the explored region of the mesosphere (between 65 and 76 km) range between 149 K and 226 K; no measurable heating is found